Cat's washer box / Mohd Kamal Hafizi Abdul Jalil...[et al.] - Abdul Jalil, Mohd Kamal Hafizi; Simon, Muhammad Rizal; Ahmad, Darwisy Muslim; Abdul Halim, Muhammad Aiman; Hasbi, Mohammad Shahrul (2019)
Felinea Sdn. Bhd. introducing a new system development which combined bathing and drying services for cat into one product. We called our product as a cat's washer box where the user can give bath to the cats and then dry them right after the bath. As we all know some cats may feel threatened and become aggressive especially when it is time for the cats to take a bath. Some of the cats might scratching or even bite us. By using our product, the user will feel much safer when it comes to bathing a cat. We have installed the shower and the blower inside the box. Plus, we provide a slot where the users can put their hands to handle the cat inside the box. This slot is covered by safety gloves which protect their hands from being scratch or bite. We made this cat's washer box transparent to make the work easier for the users. Target market is used in order to forecast business sales. From the target market, market segmentation was chosen as the market alternatives. Segmentation means that a part of a segment or a category. By using market segmentation, we can narrow down the potential customer that will purchase our product. We divided our market segmentation based on two categories that is geographic segmentation and psycho-graphic segmentation. As a starting product, our first target market is for cat's owner which is more suitable user for our product. The price for this product with installation is reasonable due to current technology and it can be buying either medium or rich people.